1972
DOI: 10.4141/cjas72-001
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Strains of Chickens to Marek’s Disease

Abstract: Fifteen strains of chickens wele tested in by contact in a controlled environment house three experiments for susceptibility to Marek's (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Post mortem examinations in the MD challenge test were similar to those described by Grunder et al (1972). MD mortality included all birds that died with gross lesions typical of MD in visceral organs, brachial and/or sciatic plexus or in muscles of breast or thighs.…”
Section: Post Mortem Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post mortem examinations in the MD challenge test were similar to those described by Grunder et al (1972). MD mortality included all birds that died with gross lesions typical of MD in visceral organs, brachial and/or sciatic plexus or in muscles of breast or thighs.…”
Section: Post Mortem Examinationsmentioning
confidence: 99%
“…All chickens in each test were randomly distributed throughout the 10 pens on the day of hatch. They were inoculated intra-abdominally at 22 days of age with blood from chickens infected with the BC-1 isolate of MD virus as described by Grunder et al (1972). The challenge tests lasted 81 and 84 days in years 1970 and 1971 respectively.…”
Section: Egg Production Test and Vaccination Against MDmentioning
confidence: 99%
“…The first investigators (Waters, 1945;Heisdorf et al, 1947) found no relationship between the two methods; later, others (Biggs et al, 1968;Schmittle and Eidson, 1968;Grunder et al, 1972) found a positive correlation. These conflicting results may have been due to confusion between visceral MD lymphomas and lymphoid leukosis, both of which were termed "lymphomatosis" by early investigators.…”
Section: Discussionmentioning
confidence: 96%
“…Based on previous studies (e.g. Grunder et al, 1972), the resistance to MD virus could be considered relatively high in strain 4, intermediate in strains 5 and K and low in strain S. Experiments 1, 2 and 3 were designed to study the effects of strain of chickens and of maternal antibody against MD associated antigens on resistance to JMV-L, JMV-H and TLT respectively. Chicks for these experiments were produced within each of the above four strains from the following three flocks of dams (originating from a common grand parental stock): (a) dams free of infection with MD virus, kept in a filtered air, positive pressure facility; (b) dams adventitiously exposed to MD, kept in a conventional facility; (c) dams vaccinated with herpesvirus of turkeys on the day of hatch and kept in the same conventional facility as dams (b).…”
Section: Lymphoid Tumor Preparations Jmv Was An MD Tumor Cell Inoculmentioning
confidence: 99%
“…White Leghorn chickens from Ottawa strains 4 and 5 (Grunder et al, 1972) and Cornell strains K and S (Hutt and Cole, 1957) were used in the study. Strain 4 had been selected for high egg production and related traits over 24 generations and its egg production was similar to that of commercial breeding stocks.…”
Section: Lymphoid Tumor Preparations Jmv Was An MD Tumor Cell Inoculmentioning
confidence: 99%